2020
DOI: 10.1016/j.drugpo.2020.102865
|View full text |Cite
|
Sign up to set email alerts
|

“Doing What Is Right and Doing It Right”: A Mapping Review of Athletes' Perception of Anti-Doping Legitimacy

Abstract: Background: The creation of the World Anti-Doping Agency in 1999 and the first implementation of the Anti-Doping Code in 2004 established institutional and legal level legitimacy for the anti-doping movement. Subsequently, a distinct line of research examining athletes' perceptions of anti-doping has emerged. This study aims to review the literature on legitimacy via athletes' perceptions of the underpinning values, fairness and effectiveness of anti-doping rules and procedures.Methods: A systematic mapping re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 67 publications
1
50
1
2
Order By: Relevance
“…Athletes' perceptions of the effectiveness and fairness of the anti-doping system has been widely studied, and the literature in that area was the subject of a recent mapping review (Woolway et al, 2020 ). It is noted in this review that the greater the extent to which an athlete views the anti-doping rules and regulations as legitimate, the more likely that athlete will be to comply with those rules and regulations.…”
Section: Introductionmentioning
confidence: 99%
“…Athletes' perceptions of the effectiveness and fairness of the anti-doping system has been widely studied, and the literature in that area was the subject of a recent mapping review (Woolway et al, 2020 ). It is noted in this review that the greater the extent to which an athlete views the anti-doping rules and regulations as legitimate, the more likely that athlete will be to comply with those rules and regulations.…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to develop fit-for-purpose education programmesand develop capability in the anti-doping systemathletes and ASP need to be engaged in the educational design and development process from the outset (Backhouse & McKenna, 2012;Petróczi et al, 2017). Involving athletes and ASP in the design and development of education programmes may increase their perceived legitimacy, and improve overall effectiveness, of the anti-doping system (Patterson et al, 2019;Woolway et al, 2020). Further education programmes need to move beyond compliance-based activities that are delivered didactically to ensuring programmes are engaging and interactive (Backhouse et al, 2009;Backhouse et al, 2014;Hallward & Duncan, 2019).…”
Section: Implications For Clean Sport Policy and Practicementioning
confidence: 99%
“…The latter explicitly recognises that clean sport comes from athletes 'being clean'. A recently completed pan-European community-based study with elite athletes and anti-doping organisations showed that whilst clean athlete identity is universally linked to rule-following and rooted in upbringing, early life experiences and love of sport, the definition of what constitute clean performance-enhancement within rulefollowing is highly idiosyncratic (Petróczi et al, 2020). This research suggests that it is the set of anti-doping rules, not the substances or methods per se, that defines clean sport behaviour for athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Doping represents a social, institutional, and moral problem which undermines the Spirit of Sport, and counters the values that underpin sport and anti-doping organizations globally (Donovan et al, 2002 ; Engelberg et al, 2015 ; Petróczi et al, 2017 ; WADA, 2021a ). Since the creation of WADA in 1999, anti-doping organizations (ADOs), at national and/or regional levels, have attempted to prevent athletes' use of doping substances and methods through increased and improved doping control procedures and the use of the Whereabouts system (Gatterer et al, 2020 ; Woolway et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Athletes, spectators, and sponsors alike desire clean and fair sport, and it is this that gives legitimacy to anti-doping efforts. These shared values and priorities render the anti-doping effort ethically justifiable (Woolway et al, 2020 ). This shared sentiment and tacit agreement about the importance of the Spirit of Sport values justify infringements and inconvenience to athletes around doping control testing, limitation on privacy and personal freedom, and underpins anti-doping education.…”
Section: Introductionmentioning
confidence: 99%